Unveiling the Sodium/Potassium Storage Mechanisms of Nanoporous Indium-Bismuth Anode Using Operando X-ray Diffraction. (1st December 2022) - Guo, Zhiyuan; Qin, Jingyu; Yu, Bin; Ma, Wensheng; Yang, Wanfeng; Cheng, Guanhua; Gao, Hui; Zhang, Zhonghua
Abstract : Sodium ion batteries (SIBs) and potassium ion batteries (PIBs) are promising post-lithium candidates for grid-scale energy storage, and understanding of the Na/K chemistry is crucial for the development of advanced electrode materials. Herein, a nanoporous indium-bismuth (np-InBi) alloy was fabricated by chemical dealloying of a ternary Mg-In-Bi precursor, and shows a three-dimensional ligament-channel structure. As the anode for SIBs and PIBs, the np-InBi alloy exhibits decent initial discharge capacity. More importantly, the Na/K storage mechanisms of the np-InBi electrode were investigated using operando X-ray diffraction (XRD). The operando XRD results demonstrate that the (de)sodiated mechanism of the np-InBi electrode in SIBs involves (de)alloying processes between InBi + Bi to Na3 Bi + Na15 In27 via the intermediate products of NaBi + Na15 In27 + In. Simultaneously, the (de)potassiated mechanism of the np-InBi electrode in PIBs yields the reversible processes of InBi + Bi ↔ KBi2 + Bi3 In5 ↔ K3 Bi + K8 In11 .